Comparison of two protocols of home-based exercise on the physical fitness of older women with breast cancer under hormonal treatment: a clinical trial - Ana Clara Carvalho Gonçalves Guerra; Guilherme Henrique de Lima Matias; Breno Augusto Bormann de Souza Filho; Érika Fernandes Tritany; Victor Rafael Fernandes da Silva; Cleber Nascimento do Carmo; João Guilherme Bezerra Alves; Jurema Telles Alves de Oliveira Lima; José Roberto da Silva Júnior (Fisioterapia e Pesquisa)
ABSTRACT This study aims to compare the effects of two home-based physical exercise protocols on the physical fitness of older women with breast cancer using hormone therapy. This is a comparison study between the effects of two clinical trials developed with patients and different execution periods, subjected to different home-based exercise protocols. In total, 68 older women, aged between 60 and 74 years old, diagnosed with breast cancer, stage I or II, were included, allocated into 2 groups. Group A (n=38) performed a protocol consisting of 29 exercises and group B (n=30) used a protocol with 12 exercises, both lasting 12 weeks and providing guidance via an introductory lecture, self-instructional material, and weekly telephone contacts. Physical fitness assessment was carried out using the Senior Fitness Test at the beginning and after the 12th week. Statistical analyzes were performed using STATA version 12, with a p<0.05 significance level. The evaluated protocols showed gains related to the components of physical fitness, range of motion and strength, with Group A showing greater gains than Group B. The choice between protocols must be made according to the adopted therapeutic objectives.